KEMAMPUAN SISWA MEMECAHKAN MASALAH HUKUM-HUKUM DASAR KIMIA MELALUI PEMBELAJARAN INKUIRI TERBIMBING - Lukman A.R. Laliyo; Mian Kau; Jafar La Kilo; Akram La Kilo (Jurnal Ilmiah Ar-Razi, 2020)
The purpose of research was to determine the problem solving skill of basic chemical laws at tenth-grade senior high school of  through the application of guided inquiry learning models. The ability is known through a three tier multiple choice diagnostic test. This research was an experimental quasi with pretest-posttest control group design. The  sample consisted of 107 students consisting of 56 experimental class  and 51 control class. Based on the results of the calculation of the F test that F count> F table (10.72> 3.93) with α = 0.05. This means that there was an influence of the application of the guided inquiry learning model to students' ability to solve problems in the basic laws of chemistry. 70.71% of students in the experimental class can understand the problem, plan the solution, carry out the solution, and re-examine the results of the problem solving. Meanwhile, control class students were unable to solve very high problems, namely 24.5% students..